PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMUNIKASI, DAN MOTIVASI DALAM RANGKA MENINGKATKAN PRODUKTIVITAS KINERJA PEGAWAI (STUDI KASUS PADA PEGAWAI KANTOR CAMAT TAMAN SARI KOTA PANGKALPINANG) - Rani, Septia; Hasianda Tigor, Ryan; Oktalina, Gayatria (STIE IBEK Pangkalpinang, 2022)
This research was entitled in Bahasa Indonesia: “Pengaruh kualitas Sumber Daya Manusia, komunikasi, Dan Motivasi Dalam Rangka Meningkatkan Produktivitas Kinerja Pegawai (Studi Kasus pegawai Kantor Camat Taman Sari Kota Pangkalpinang)”. This research was conducted during the pandemic of Covid-19 (Maret 2022-June 2022) and it was administrated in the City of Pangkalpinang. The purpose of this study was to determine how strong the effect of the Quality of human resources, Communication, and Motivation is on Employee performance and productivity. This study runs by using quantitative data analysis and was using a Multiple Linear Regression Analysis along with a Coefficient of Determination. The results of the analysis state that the Quality of human resources variable has no effect on employee performance with the results (t-count (3.245) while t-table 1,705), in other words (t-count value (3.245) > t-table value 1,705) or value of significance 0,004 < 0,05 then clearly H1 is accepted. The results of the analysis state that the Communication variable has a positive effect on Employee performance with the results (t-count (3.121) while t-table 1,705), in other words (t-count value (3.121) > t-table value 1,705) or value of significance 0,001 < 0,05 then clearly H2 is accepted. The results of the analysis state that the Motivation variable has positif effect on Employee performance Productivity with the results (t-count (3.307) while t-table 1,705), in other words (t-count value (3.307) > t-table value 1,705) or value of significance 0,003 < 0,05 then clearly H3 is accepted. As simultaneously or together, it shows that the variables of Quality of human resources, Communication, and Motivation have a significant effect on Employee performance productivity with the results of F-count 34.186 and F-table value of 2,98. In other words, Fcount (34.186) > Ftable (2,98).), therefore it is shown that H0 is rejected and H4 is accepted. With the coefficient of determination obtained a value of 0,797, which means that the effect of the independent variables on dependent variable simultaneously at 79,7%, and the remaining 20,3% is explained by other independent variables not used in this study.